Pinocchio (Manila : WS Pacific Publications, 2023)
A wooden puppet must earn the right to be a real boy by proving that he is brave, truthful, and unselfish.
Pop-up board book.
Keywords: Children's stories; Toy and movable books -- Specimens; Fairy tales